Pengoptimalan Waktu Terhadap Hasil Adukan Pada Alat Pengaduk Bahan Dasar Sabun Cair - Rahmadsyah; Andri Ramadhan; Moraida Hasanah; Soleh Solahuddin (G-Tech: Jurnal Teknologi Terapan, 2023)
The liquid soap base mixing machine is a machine whose working principle utilizes power from an electric motor and is transmitted to the pulley and v-belt mechanism. The power generated by the electric motor will be transferred to the shaft which is connected to the stirring rod. Pulleys and belts are a pair of machine elements used to transmit power from one shaft to another. The speed ratio between the drive shaft and the driven shaft depends on the diameter of the driven pulley.